Research of Inseam Horizontal Drainage for Coalbed Methane Production - Zhao, Zidong (Curtin University, 2019)
During the full-time of two-year research, the primary objectives are focused on coal-bed methane elimination in underground coal mines, especially for in-seam horizontal methane drainage. Firstly, this research reviewed the method of in-seam horizontal drainage within 6 controllable factors. Secondly, this research also improved the methane drainage system which applied in a coal mine in China with the basic theory. In addition, some factors of gas related disasters are investigated as preliminary work for CBM.